(untitled) - Manal Rashid Taqatqa (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Purpose: The study investigates the differences between low-status versus high-status expatriates as perceived by Saudi Arabian human resources managers. The purpose is to identify the differences of perceptions of Saudi HR managers when hiring and evaluating American versus Indian expatriates. Methodology: The study has used Qualitative, hermeneutic phenomenology that has helped in gaining a better idea of the process leading to investment in a new mechanism to deal with the prospect of the research. Interview has been done on 19 Human Resource Managers of Saudi Arabia who has more than one-year experience. Data has been analyzed with the help of thematic coding analysis. Findings: Based on the data gathered from respondents, it has been found that, Saudi HR managers evaluate American expatriates differently than evaluating Indian expatriates. Salaries offered to equally qualified expatriates differ as well. They also believe Indian expatriates have higher commitment work assignments than Americans and the two groups may influence organizations differently. Saudi HR managers think American expatriate will provide more standards their Indian expatriate will provide more products in the organization. It was also observed that, Saudi HR managers believe American expatriates care about work ethics more than Indian expatriates. Originality: Primary data has been gathered from participants in this interview. Very few statistics have been gathered based on American and Indian expatriates to understand the research topic well. Keywords: Expatriates, hermeneutic qualitative research, compensation equality, cross-cultural adjustments